2011
DOI: 10.1111/j.2044-8279.2011.02034.x
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive correlates of mathematical achievement in children with cerebral palsy and typically developing children

Abstract: Impairments of non-verbal IQ and WM updating predicted future difficulties in both word-problem solving and reading. Impairments of visuospatial sketchpad and inhibition predicted future word-problem, but not reading difficulty. Conversely, deficits of phonological loop predicted reading but not word-problem difficulty. Concurrent arithmetic fact fluency and reading ability were both important for word-problem solving ability. These results could potentially help to predict which children are likely to develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 44 publications
(56 reference statements)
1
36
0
Order By: Relevance
“…The identification of low matrices scores in children with CP is consistent with other studies which have used the RPM/RCPM (Jenks et al, 2012;Peeters et al, 2008). Our findings are also consistent with the evidence that children with CP have better receptive language than non-verbal ability as assessed by matrices tasks (Bishop et al, 1990;Dahlgren Sandberg, 2001).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The identification of low matrices scores in children with CP is consistent with other studies which have used the RPM/RCPM (Jenks et al, 2012;Peeters et al, 2008). Our findings are also consistent with the evidence that children with CP have better receptive language than non-verbal ability as assessed by matrices tasks (Bishop et al, 1990;Dahlgren Sandberg, 2001).…”
Section: Discussionsupporting
confidence: 91%
“…Available research has shown that children with CP are more likely to experience difficulties with mathematical learning than TD children (Frampton, Yude, & Goodman, 1998), and a small number of studies have highlighted that children with CP are often delayed in acquiring numerical skills such as: subitizing (quantifying sets); counting; and basic arithmetic problem-solving (Jenks, van Lieshout, & de Moor, 2012;van Rooijen et al, 2012). In a longitudinal study over two years, van Rooijen et al (2014) found that those children with CP and higher non-verbal intelligence increased their mathematical skills on a trajectory similar to a comparison group of TD children; however, they did not catch up with their TD peers.…”
Section: Mathematical Abilities Visual-spatial Abilities and Cerebrmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies with children older than 9 years have included measures from each of the three EF domains (Jenks, van Lieshout, & de Moor, ; Lee et al., ; Rose, Feldman, & Jankowski, ; St Clair‐Thompson & Gathercole, ; van der Sluis, de Jong, & van der Leij, ). Two studies assumed a single‐factor EF latent (Neuenschwander et al., ; Roebers et al., ) and found that EF had a direct effect on mathematics achievement as assessed by curriculum‐based tests, teacher grades, and behaviors related to classroom learning.…”
Section: Exploratory and Confirmatory Studies Of The Role Of Ef In Mamentioning
confidence: 99%
“…For example, visual learning is an special learning procedure for ADHDs. Arithmetical cognitive functions are poor for children with learning di±culties, children with dyscalculia (Kaufmann & von Aster, 2012) and cerebral palsy patient (Jenks et al, 2012) groups, which can be improved by education input and attention by Wooden Fraction set in which fractions use a different bright colored wood block shapes which are fun for learning. Still there is no research publication on the rehabilitation use of wooden fraction set and this use con¯ned within occupational therapists only.…”
Section: Introductionmentioning
confidence: 99%